2013
DOI: 10.1055/s-0033-1344583
|View full text |Cite
|
Sign up to set email alerts
|

Data quality of the German Screening Colonoscopy Registry

Abstract: Of the screening colonoscopy quality parameters, colonoscopy completion rate and ADR, but not complication rates, were reliably documented in the German national screening colonoscopy registry. Data on complications need to be appropriately standardized and audited in order to be used for credentialing and benchmarking purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 26 publications
2
43
0
1
Order By: Relevance
“…There are initiatives from various countries to audit and monitor colonoscopy quality and auditing programmes 93 100–102. The Asia Pacific Consensus group strongly believes that an audit system should be introduced in each country or region on the quality of colonoscopy.…”
Section: How To Minimise Missed Lesions or Interval Cancers?mentioning
confidence: 99%
“…There are initiatives from various countries to audit and monitor colonoscopy quality and auditing programmes 93 100–102. The Asia Pacific Consensus group strongly believes that an audit system should be introduced in each country or region on the quality of colonoscopy.…”
Section: How To Minimise Missed Lesions or Interval Cancers?mentioning
confidence: 99%
“…Details of the registry's operation and data quality have been reported elsewhere. 14,16 Briefly, all screening colonoscopies are reported anonymously on a standardized form. Reporting is virtually complete, as it is a prerequisite for physicians' reimbursement by the health insurance funds.…”
Section: Databasementioning
confidence: 99%
“…Concerning the German screening colonoscopy registry (to which the underlying data also contributed), a recent study indicated that the ADR is generally reliably documented, and data quality problems might therefore not have affected the current data to a large extent. 33 In addition to age and sex, further confounding factors could be taken into account in the case-mix adjustment. These include in principle all risk factors for colorectal neoplasia such as behavioral factors, personal and family history of colorectal neoplasia, inflammatory bowel disease, race, and ethnicty.…”
Section: Discussionmentioning
confidence: 99%